Can a river be an actor? Rethinking human–non-human relations in the ecological epistemology of the Semende indigenous community - Lestari, Widya; Amriani, Nita; Wole, Murniyati Putri; Fitriah, Putri Athifah; Ramadhani, Ikrana (Research Journal in Advanced Humanities, 2026)
This study examines how the Semende Indigenous community in South Sumatra understands rivers as spiritual actors and how their ecological practices reflect the interconnected relationship between humans and non-humans. The study employs a qualitative approach using a literature review method that analyzes literature on Actor-Network Theory (ANT), Indigenous ecological knowledge, environmental reports, and studies on the Semende community. The findings show that through the Tumutan Tujuh tradition, the Semende people regard rivers as sacred living entities with spiritual agency that play an important role in sustaining social, ecological, and spiritual life. This understanding is reflected in customary regulations, rituals honoring water sources, the protection of upstream areas, and the role of customary leaders in maintaining environmental sustainability. From the perspective of ANT, rivers function as non-human actors that shape community values, norms, and social practices. The study also reveals that humans, rivers, forests, plants, and animals are understood as interconnected parts of a shared ecological network. These findings highlight the contribution of Indigenous ecological knowledge to environmental conservation and offer an ecological justice paradigm that recognizes non-human agency.